Genitourinary radiology cases - Lockhart, Mark E.; Sanyal, Rupan (Cases in radiology., 2014)
In 129 cases featuring over 600, high-quality images, Genitourinary Imaging Cases provides a succinct review of clinically relevant cases which cover both benign and malignant conditions of the genitourinary system. Cases are grouped into sections that are organized by body part including: Kidney, Retroperitoneum, Adrenal, Ureter, Bladder, Prostate, Urethra, Vagina, Penis, Testis, Epididymis, and Scrotum, Uterus and Fallopian Tube, and Ovary. Part of the Cases in Radiology series, this book follows the easy-to-use format of question and answer in which the patient history is provided on the first, and radiologic findings, differential diagnosis, teaching points, next steps in management, and suggestions for furthering reading are revealed below.